Cerebral Palsy is not a choice, but acceptance is (Journal of Pakistan Orthopaedic Association, 2020)
Cerebral Palsy (CP) is caused by a non-progressive lesion to an immature brain and results in different types of neurological problems including spasticity, motor weakness, poor coordination, dystonia and ataxia. Spasticity is the commonest type of problem seen in CP.            The primary neurological damage in CP results in abnormal tones, selective control, coordination and motor imbalance. The mainstay of treatment in the first 6-7 years of age is tone management and physical therapy. The primary neurological problem is static but the muscles and bones are under the influence of abnormal muscle tone and muscle imbalance during growth, secondary problem (musculoskeletal) such as torsional deformities of long bones and contractures of muscle and joint develops with time. Contractures, joint stiffness and subluxation becomes more obvious and compromise walking after the age of 7-8 years. Orthopaedic intervention to correct these secondary skeletal deformities starts to play a more important role after this age.